The problem with inclined derivative for a parabolic equations with impulse conditions and degeneration - Pukalskiy, I.D. (Carpathian Mathematical Publications, 2014)
By application of maximum principle and apriori estimates it is studied the inclined derivative problem for a linear parabolic equation with power singularity in the coefficients with respect to space variables and impulse conditions respect to time variable. It is established the uniqueness and the existence of the solution of the stated problem in Holder spaces.